Using Compartments to Model Drug Delivery from Biodegradable Polymers; Journal of Pharmaceutical Sciences; Vol. 111, iss. 11 - Marriott R.; Spiridonova T. I. Tatjyana Igorevna; Tverdokhlebov S. I. Sergei Ivanovich; Anisimov Yu. G. Yury German (2022, 2022)
Title screen